PENGEMBANGAN KECERDASAN INTELEKTUAL MENURUT AL-QUR'AN - M.F. HIDAYATULLAH (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
This paper tries to reveal the development of the intellectual intelligence based on the Qur'an, by using Tafsir Maudhu'i method based on Surah Al'Alaq verse 1-5. This understanding is important because of the fact that SurahAl-'Alaq: 1-5 are the first verses that were given down and ordered for the Muslims to read. To develop the intellectual, in this Surah, Allah tells Muslims to read, to communicate, to analyze, to explore, and to examine the Qur'an and the universe. The reading should be based on the name of Allah so that it will improvw the faith in Allah. Key words: the intellectual intelligence, the Qur'an, tafsir maudhu'i